Health worker adherence to malaria treatment guidelines at outpatient health facilities in southern Malawi following implementation of universal access to diagnostic testing. (December 2017) - Namuyinga, Ruth; Mwandama, Dyson; Moyo, Dubulao; Gumbo, Austin; Troell, Peter; Kobayashi, Miwako; Shah, Monica; Bauleni, Andrew; Eng, Jodi; Rowe, Alexander; Mathanga, Don; Steinhardt, Laura
Abstract Background Appropriate diagnosis and treatment are essential for reducing malaria mortality. A cross-sectional outpatient health facility (HF) survey was conducted in southern Malawi from January to March 2015 to determine appropriate malaria testing and treatment practices four years after implementation of a policy requiring diagnostic confirmation before treatment. Methods Enrolled patients were interviewed, examined and had their health booklet reviewed. Health workers (HWs) were asked about training, supervision and access to the 2013 national malaria treatment guidelines. HFs were assessed for malaria diagnostic and treatment capacity. Weighted descriptive analyses and logistic regression of patient, HW and HF characteristics related to testing and treatment were performed. Results An evaluation of 105 HFs, and interviews of 150 HWs and 2342 patients was completed. Of 1427 suspect uncomplicated malaria patients seen at HFs with testing available, 1072 (75.7%) were tested, and 547 (53.2%) tested positive. Testing was more likely if patients spontaneously reported fever (odds ratio (OR) 2.6; 95% confidence interval (CI) 1.7–4.0), headache (OR 1.5; 95% CI 1.1–2.1) or vomiting (OR 2.0; 95% CI 1.0–4.0) to HWs and less likely if they reported skin problems (OR 0.4; 95% CI 0.2–0.6). Altogether, 511 (92.7%) confirmed cases and 98 (60.3%) of 178 presumed uncomplicated malaria patients (at HFs without testing) were appropriately treated, while 500 (96.6%) of 525 patients with negative tests did not receive anti-malarials. Only eight (5.7%) suspect severe malaria patients received appropriate pre-referral treatment. Appropriate treatment was more likely for presumed uncomplicated malaria patients (at HFs without testing) with elevated temperature (OR 1.5/1 °C increase; 95% CI 1.1–1.9), who reported fever to HWs (OR 5.7; 95% CI 1.9–17.6), were seen by HWs with additional supervision visits in the previous 6 months (OR 1.2/additional visit; 95% CI 1.0–1.4), or were seen by older HWs (OR 1.1/year of age; 95% CI 1.0–1.1). Conclusions Correct testing and treatment practices were reasonably good for uncomplicated malaria when testing was available. Pre-referral treatment for suspect severe malaria was unacceptably rare. Encouraging HWs to elicit and appropriately respond to patient symptoms may improve practices.